POTENSI WISATA SPIRITUAL ALAS METAPA DESA PENINJOAN, KECAMATAN TEMBUKU, KABUPATEN BANGLI - I Ketut Muliadiasa; Ida Bagus Made Wiyasha; Ni Putu Isha Aprinica (UHN IGB Sugriwa Denpasar, 2022)
At this time Peninjoan Village, Tembuku District has been declared a Nature Tourism Village. This is inseparable from the potential for natural tourism such as hills, springs, and various other natural potentials. Various efforts have been made in an effort to utilize the various potentials and products that exist in the spiritual nature tourism of Alas Metapa, fix inequalities and take advantage of various opportunities and overcome threats. Development that focuses on the utilization of existing spiritual natural tourism products has not been maximally carried out. Even now, the utilization of spiritual nature tourism on the pedestal of metapa has not reached the desired target. The urgency of this research is 1) To identify the level of spiritual tourism potential of pedestals in Peninjoan Village, Tembuku District, Bangli Regency. 2). To formulate a strategy for developing Alas Metapa Spiritual Tourism in Peninjoan Village, Tembuku District. Data collection techniques used were observation, interviews, documentation studies and questionnaires. The data analysis technique used triangulation analysis with SWOT matrix and ADO-ODTW natural tourism potential checklist. The results of this study reveal the level of tourism potential in Peninjoan village and alternative development models that can be applied in managing the Peninjoan tourist village